Kepler's cosmological synthesis : astrology, mechanism and the soul - Boner, Patrick (History of science and medicine library, 2013)
Spanning the course of his career, this book brings new light to Kepler's vitalistic views and their central place in his world picture. It challenges our view of Kepler as a nascent mechanical philosopher who fell back on an older form of physics.